Implementasi Kebijakan Pendidikan Karakter Islami di SMA Budisatrya - Rizki Akmalia; Khoirunnisa Fadila; Marhatul Fatwa; Hafiz Yusuf Nasution; Faradillah Amelia (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2024)
Character education is an important foundation in the formation of a young generation that is not only academically intelligent but also noble. SMA Budisatrya is committed to implementing character education through the integration of moral values into the curriculum and school culture. This approach aims to create individuals with integrity, responsibility and the ability to face the challenges of the modern era. This study aims to analyse the implementation of the character education policy at Budisatrya High School, including the strategies used and the challenges faced. This research uses a qualitative approach with data collection techniques through interviews and observations at Budisatrya High School. The research informants consisted of the principal and teachers. The implementation of character education at Budisatrya High School is carried out through school culture such as 5S (smile, greeting, greeting, politeness, courtesy) and the Pancasila Student Profile Strengthening Project (P5) programme. Challenges faced include the diversity of student backgrounds, time constraints, and the influence of social media. Collaboration between school, family and community is an important factor in ensuring consistency in the implementation of character values. Evaluation results show that the implemented character education is able to create a more conducive school environment and encourage students to practice moral values in their daily lives.